Explaining the emergence of low carbon forerunner cities based on the interaction effects of different governance processes: a case study of China's low carbon pilot - Qianqian Wei (Carbon Management, 2021)
Although growing attention has been paid to the role of cities as agents for driving transformative low carbon transition, empirical work in this field suggests that urban carbon reduction responses vary significantly. In order to shed light on why cities perform differently and why radical changes rarely take place at the city level, this study builds on the multilevel governance framework and draws attention to interaction effects between the three well-recognised governance processes: central-local interaction, transnational networks, and local networks. It is argued that understanding the interaction effects can not only help us better apprehend the longitudinal process by which low carbon actions were materialised in cities, but also contributes to identifying pathways by which urban carbon reduction responses were invoked in different socio-political contexts. Empirically, the interaction effects were explored through an in-depth case study of a Chinese low carbon forerunner city Guangzhou. Material for the case study comes from 32 semi-structured interviews with key actors from both government and non-governmental sectors carried out in 2017. Three mechanisms were outlined to illustrate the linear relationships between different governance processes which turned Guangzhou into a low carbon forerunner. Furthermore, based on the positive reading of the findings, a self-reinforced framework which is able to facilitate continuous progress and more radical changes was developed. This self-reinforced framework not only serves a normative purpose to guide future interventions on urban low carbon transition, but also provides insights into why transformative changes rarely emerge bottom-up by showing how difficult it is to sustain its function over time.